2009
DOI: 10.1016/j.canlet.2008.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer metastasis suppressor 1 (BRMS1) suppresses metastasis and correlates with improved patient survival in non-small cell lung cancer

Abstract: Breast cancer metastasis suppressor 1 (BRMS1) is a metastasis suppressor gene in several solid tumors. The role of BRMS1 in non-small cell lung cancer (NSCLC) is not well established. To assess in vitro and in vivo metastatic behavior H1299 NSCLC cells stably expressing BRMS1 or a vector control were created. BRMS1 expression significantly decreases both migration and invasion of NSCLC cells in vitro. Importantly, in flank xenografts, BRMS1 suppresses the formation of pulmonary and hepatic metastases but does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
86
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(103 citation statements)
references
References 27 publications
13
86
1
1
Order By: Relevance
“…Of these tumor samples, 5 had lymph node metastasis, and 5 did not. Consistent with our previous findings (18,25), BRMS1 was downregulated in all 10 tested NSCLC samples compared with levels in adjacent tissue (Fig. 7A).…”
Section: Knockdown Of Twist1 Abrogates the Brms1supporting
confidence: 81%
See 4 more Smart Citations
“…Of these tumor samples, 5 had lymph node metastasis, and 5 did not. Consistent with our previous findings (18,25), BRMS1 was downregulated in all 10 tested NSCLC samples compared with levels in adjacent tissue (Fig. 7A).…”
Section: Knockdown Of Twist1 Abrogates the Brms1supporting
confidence: 81%
“…The breast cancer metastasis suppressor 1 gene (BRMS1) is a metastasis suppressor gene that significantly reduces intratumoral expression in NSCLC, compared with that in adjacent tissue (17,18). Importantly, we have shown that the reduction of BRMS1 expression at protein and mRNA levels significantly correlates with NSCLC progression and poor prognosis (18).…”
mentioning
confidence: 89%
See 3 more Smart Citations